Photovoltaic energy to improve energy efficiency in homes and buildings: RSL - Carmin Silva , Eduardo Romulo (2023)
Solar energy is considered one of the most important energy sources in recent years and is used by photovoltaic panels for electricity generation, making it a valuable alternative to generate quality, stable energy and improve energy efficiency in a residence. Specifically, the study of implementing solar panels as electricity generating alternatives in homes is very important. Taking into account the above, the purpose of this research work is to present a current perspective on commonly standardized installations and innovative methodologies that use photovoltaic energy, highlighting the growth and effectiveness in other parameters such as quality, energy efficiency and others in the home energy field. The study carried out focuses on the RSL, following the procedure set by the PRISMA matrix with a representative sample of 81 articles from the Scopus and Scielo data source between the years 2019 and 2023. The results demonstrate that using photovoltaic energies provides benefits. and that help buildings and homes partially and/or completely fulfill their load as sustainable solar energy generation technologies. The findings suggest that researchers agree that the implementation of photovoltaic systems considerably improves the energy quality (33% increase) and energy efficiency (23% increase) in a residence, as well as highlighting the greatest benefit of the implementation of an isolated system in almost 44% of the articles, also considering the various data collection methods and testing mechanisms